Exploring Retailer’s Grocery Purchasing Behavior through Online Platforms in Bengaluru City, India - Abhishek S; Deval B Patel (Archives of Current Research International, 2024)
Indian retail market is one of the most complicated and dynamic industry which is contributing to more than 10% of the country’s gross domestic product (GDP) and around 8% of the employment. Mainly it is dominated by unorganized retailers, in last 10 years gradual shifts, like entry of modern trade, the entry of cash and carry, the advent of the e-commerce revolution and, more recently, the growth in newage B2B providers have started to transform this ecosystem, this makes retailers to go for online purchase of grocery using e- B2B platforms. Keeping this background in mind, the study was conducted in Bengaluru city with sample size of 250 retailers using primary as well as secondary data. The data was analysed using percent analysis, frequency, weighted average mean and Garrett ranking method. The study reveals that retail sector in study area is dominated by male ownership, most of the retailers were aged above 45 years having basic level of education and have more than 15 years of experience in retailing. Factors such as convenience, price, and wide product availability are the primary factors influencing online purchases, with convenience having the highest WAM score 4.2. All the surveyed retailers are aware of online grocery applications, indicating a high penetration of digitalization in the area. Retailers predominantly order once or twice a week, with most orders value between 700-3000 rupees, reflects the use of online platforms for regular stock replenishment. Main problems faced by retailers were delivery of damaged product, return issues and minimum order value and these were the main factors influencing them to stay away from online purchase.